2022
DOI: 10.3390/su142416922
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Robust Optimization of Scheduling and Signal Timing for Bus Rapid Transit

Abstract: The unbalanced nature of passenger demand and the uncertainty of delay at intersections are considered critical factors in the efficiency of public transportation operations. Considering the controllable characteristics of the bus rapid transit system (BRT), an integrated optimization model that includes multi-mode transit scheduling and signal timing is proposed. The robust optimization model copes with the fluctuations in passenger demand and bus operation. A non-linear programming is developed to minimize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Another approach was proposed by Xue et al [18] in which they used uncertainty theory and a bilevel programming model to optimize the frequency and time between departures of the 207 bus routes of Nanchang city, China; they demonstrated that this is an effective approach for reducing passengers' travel times, but it has some limitations. Wang et al [19] proposed a mixed integer nonlinear programming model in which they sought to optimize bus schedules and traffic signaling. To analyze the model, they considered the Fengpu BTR line in Shanghai, China and showed that the passengers' traveling times could be decreased compared to a more traditional approach.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach was proposed by Xue et al [18] in which they used uncertainty theory and a bilevel programming model to optimize the frequency and time between departures of the 207 bus routes of Nanchang city, China; they demonstrated that this is an effective approach for reducing passengers' travel times, but it has some limitations. Wang et al [19] proposed a mixed integer nonlinear programming model in which they sought to optimize bus schedules and traffic signaling. To analyze the model, they considered the Fengpu BTR line in Shanghai, China and showed that the passengers' traveling times could be decreased compared to a more traditional approach.…”
Section: Introductionmentioning
confidence: 99%